Evidence of Circumstances of The Civil Case: Right or Duty? - Андрійцьо, В. Д. (Theory and practice of jurisprudence, 2016)
In this article the author examines the essence and meaning of general rule of the process of the segregation of evidence duties that operates under the establishing circumstances of the civil case. On the basis of the materials, it is concluded that the evidence is the duty that is executed by persons who are involved in a civil case by alternative ways and in certain procedural forms.